2016
DOI: 10.1021/acs.jpcc.6b04262
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Anion Effect on Nanostructural Organization of Dicationic Imidazolium-Based Ionic Liquids

Abstract: This work reports the influence of anion structure (Br -, NO 3 -, BF 4 -, and SCN -) in the aggregation process of ionic liquids (ILs), derived from 1,8-bis(3-methylimidazolium-1-yl)octane, in 4.75% ethanol-water solution (v/v). The aggregation behavior was investigated using small angle x-ray scattering (SAXS), nuclear magnetic resonance (NMR), dynamic light scattering (DLS), and transmission electron microscopy (TEM). Spin-lattice relaxation times (T1), obtained by NMR, indicated that the molecular mobility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
(121 reference statements)
0
20
0
Order By: Relevance
“…1,2 Depending of the cation and anion combination, ILs may exhibit different physicochemical properties when compared with conventional electrolytes media or organic solvents. [3][4][5] Properties such as high thermal stability, tunable electrochemical window, low flammability, broad liquid range, and ability to dissolve and stabilize a wide range of materials allow ILs to be used in engineered materials synthesis. Imidazolium-based ILs are among the most studied classes of ILs.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Depending of the cation and anion combination, ILs may exhibit different physicochemical properties when compared with conventional electrolytes media or organic solvents. [3][4][5] Properties such as high thermal stability, tunable electrochemical window, low flammability, broad liquid range, and ability to dissolve and stabilize a wide range of materials allow ILs to be used in engineered materials synthesis. Imidazolium-based ILs are among the most studied classes of ILs.…”
Section: Introductionmentioning
confidence: 99%
“… 21 , 28 In a recent study published by our research group, it was observed that the anions (Br, NO 3 , SCN, and BF 4 ) of [BisOct(MIM) 2 ][2X] do not influence the hydrodynamic radius of the aggregates in a solution (determined by dynamic light scattering) at different concentrations (50, 300, and 500 mM). 31 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was found that alkyl chains are folded and cationic heads interact by CH···π at the aggregate surface. 23 We expect dicationic IL aggregates in an ethanol–water solution (1–1, v/v) to be organized in a similar way, including [BisOct(BnIM) 2 ][2Br]. Therewithal, it can be concluded that API molecules can strongly affect the interactions between cationic heads when compared with self-assembly, in which the head groups organize themselves to interact effectively with APIs.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 Dicationic ILs consist of a doubly charged cation linked by a spacer chain. 23 These ILs with a long spacer chain (e.g., 8 and 10 carbons) possess excellent surface activity properties and are capable of forming aggregates in solution. 24,25 Because of such characteristics, this new class of ILs is comparable with traditional surfactants and can be used, with advantages, in the same applications as monocationic structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation